Treatment effects of fibrinogen concentrates vs. cryoprecipitate for correcting hypofibrinogenemia in cardiac surgery patients: a systematic review and meta-analysis - Chen, Yue; Yang, Wenjie; Zhao, Chongyang; Wang, Fujue; Ren, PengWei; Liu, Xuemei; Cao, Tingyong; Ji, Shuming; Chen, Lei; Kang, Deying (Frontiers in Cardiovascular Medicine, 2025)
BackgroundHypofibrinogenemia in cardiac surgery increases bleeding risk, but the efficacy and safety of fibrinogen concentrate vs. cryoprecipitate remain unclear. This meta-analysis compares the patient-important outcomes associated with the use of fibrinogen concentrate vs. cryoprecipitate for the management of acquired hypofibrinogenemia in cardiac surgery.MethodsMedline, Embase, Cochrane Library, and Transfusion Evidence Library were searched from their inception until June 2024. Eligible studies included randomized clinical trials (RCTs). Effect estimates were synthesized using risk ratios (RR) and standardized mean differences (SMD), along with their corresponding 95% confidence intervals (CIs).ResultsWe analyzed 4 RCTs (945 participants: 823 adults, 122 children) comparing fibrinogen concentrate with cryoprecipitate undergoing cardiac surgery. Meta-analysis showed no difference in mortality (RR = 1.25, 95% CI: 0.79–1.96; moderate GRADE), blood loss (SMD = −0.14, 95% CI: −0.46–0.18), transfusion rates (blood cells: RR = 0.98, 0.77–1.26; platelets: RR = 0.17, 0.02–1.40; fresh frozen plasma: RR = 0.48, 0.16–1.45; cryoprecipitate: RR = 1.02, 0.58–1.81), infections (RR = 0.91, 0.64–1.28), volume overload (RR = 1.95, 0.18–21.34), transfusion reactions (RR = 0.98, 0.06–15.54), or postoperative thrombosis (RR = 0.76, 0.47–1.22). No allergic reactions were reported. Subgroup analysis revealed substantial heterogeneity (I2 = 0% to 98%) in most outcome measures between adults and children. Using the GRADE criteria, we assessed the quality of the evidence for mortality as moderate, whereas the quality of evidence for other outcomes was judged to be low.ConclusionsFor patients undergoing cardiac surgery who experience clinically significant bleeding and hypofibrinogenemia, the available trial data provide moderate evidence that fibrinogen concentrate, compared to cryoprecipitate, does not increase the short-term risk of all-cause mortality. However, for the rate of transfusion of allogeneic or individual blood components, and adverse events, the existing evidence is of low certainty. Given the relatively small sample size, the group of children may not be representative of all children.Systematic Review Registration(https://www.who.int/clinical-trials-registry-platform), identifier CRD42023421670.